A randomised controlled feasibility study of the Carers-ID intervention to support the mental health of family carers of people with intellectual disabilities - Rachel A. Leonard; Maria Truesdale; Michael Brown; Lynne Marsh; Stuart Todd; Nathan Hughes; Trisha Forbes; Ashleen Crowe; Mark A. Linden (PLoS ONE, 2026)
Background Intellectual disability (ID) refers to significant limitations in intellectual and adaptive functioning beginning in childhood. Globally, ID affects 1–3% of the population—over 200 million people. Family carers of individuals with ID experience high levels of stress, poor health, and reduced quality of life due to ongoing caregiving demands. These pressures intensified during the COVID-19 pandemic, prompting the development of Carers-ID, an online intervention designed to support carers’ mental health. Objective To assess the feasibility of delivering the Carers-ID programme to family carers of people with ID. Methods A parallel randomised controlled trial was conducted to evaluate recruitment and retention rates, feasibility of data collection, and potential effect sizes. Carers were recruited via UK-based voluntary organisations and NHS learning disability teams and randomly assigned to either the Carers-ID intervention (n = 51) or waitlist control (n = 48). Randomisation was conducted by an independent third party. The intervention spanned two weeks with assessments at baseline, post-intervention, and three-month follow-up. Outcomes included measures of well-being, resilience, social connectedness, depression, anxiety, and stress. The trial followed CONSORT reporting guidelines. Results Of 150 carers screened, 99 met inclusion criteria, and 84 completed the baseline assessment (85%). Retention was 55% post-intervention and 41% at three-month follow-up. Adjusted mean differences between-groups at T2 (2 weeks from baseline) across the four measures were as follows: 3.42 (SE = 2.84, p = 0.23) for wellbeing, 12.20 (SE = 5.83, p = 0.04) for resilience, 5.09 (SE = 5.12, p = 0.32) for social connectedness, 0.98 (SE = 1.40, p = 0.49) for depression, 0.42 (SE = 1.26, p = 0.74) for stress, and 1.06 (SE = 1.32, p = 0.43) for anxiety. Conclusion Family carers face time and resource pressures which may exclude them from clinical trials. Challenges in retaining carers highlight the need for flexible intervention formats. Despite retention issues, results suggest feasibility in delivering the Carers-ID intervention. Future effectiveness trials should address barriers to participation and tailor interventions for this underserved population. Trial registration ClinicalTrials.gov: NCT05737823